Redesign E-learning with User Centered Design Method for Improved Accessibility Students - Khusnan Hafidz, Harvian; Lukmana Sardi, Indra; Wibowo, Yanuar Firdaus Arie (STMIK Budi Darma, 2024)
E-learning is learning with information technology in providing material and interaction between teachers and students. In the application of e-learning must have easy access for students and teachers because it will affect teaching and learning activities. However, in the application of e-learning, there are still difficulties felt by students as has been implemented in MTsN 16 Jakarta. Based on questionnaires and interviews conducted at the beginning of the study which was attended by 30 respondents obtained results where the e-learning used had difficulty in finding assignment forms, task deadlines, and discussion forums by obtaining an SUS score of 42.9. In this case, a redesign is needed to solve the problems perceived by the user. This research uses user-centered design (UCD) in design development because UCD focuses on users to meet user needs and can improve the ease of accessing e-learning based on user needs, in addition to the development of redesign e-learning will take references based on users and e-learning that has been used before. The e-learning redesign prototype will be tested using the System Usability Scale (SUS) followed by 61 respondents. From the test results using SUS got a result of 80,82 which is included in the good and acceptable category. This research also shows that redesigning e-learning using UCD can facilitate access and learning activities carried out by students